Testicular Torsion with Intact Blood Flow: A Point of Care Ultrasound Case-Series - Eric Scheier (POCUS Journal, 2024)
Studies have demonstrated the high sensitivity and specificity of pediatric emergency department (PED) point of care ultrasound (POCUS) in the evaluation of testicular torsion. Rarely, testicular torsion may present with intact blood flow. Here, we present a case series of four children with testicular torsion confirmed intraoperatively, who had intact blood flow on POCUS. Markers of testicular torsion can include surrounding hydrocele, heterogenous echotexture, absent venous or high resistance arterial flow, or a torsed cord complex. POCUS practitioners should be familiar with these findings, and the presence of any one or more of these findings should prompt urgent urology consultation to avoid missed torsion.